2021
DOI: 10.1101/2021.12.27.474262
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frontal cortical regulation of neurogenesis and cellular proliferation in the ventral subventricular zone

Abstract: The maintenance and differentiation of the adult neural stem cells (NSCs) in the subventricular zone (SVZ) are controlled by cell-intrinsic molecular pathways that interact with extrinsic signaling cues. How neurogenesis in the SVZ is regulated by neural circuit activity remains poorly understood. Here we identified a novel neural circuit that regulates the state of lateral ventricular wall (LV) NSCs. Our results demonstrate that direct glutamatergic inputs from the frontal cortex, as well as local inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Our previous studies have demonstrated that stimulating the ACC-subep-ChAT + circuit for a day leads to an increased proliferation of LV NSCs in close proximity to the subep-ChAT + neurons (27). In order to investigate the molecular mechanism responsible for the circuit’s impact on cellular proliferation, we first used optogenetics to directly manipulate subep-ChAT + neurons in this circuit for 6 hours only.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous studies have demonstrated that stimulating the ACC-subep-ChAT + circuit for a day leads to an increased proliferation of LV NSCs in close proximity to the subep-ChAT + neurons (27). In order to investigate the molecular mechanism responsible for the circuit’s impact on cellular proliferation, we first used optogenetics to directly manipulate subep-ChAT + neurons in this circuit for 6 hours only.…”
Section: Resultsmentioning
confidence: 99%
“…The subep-ChAT + neurons, a cholinergic population in the SVZ, regulate LV NSCs proliferation in an activity-dependent manner (26). Furthermore, these local cholinergic neurons receive inputs from both local GABAergic and cingulate glutamatergic neurons, which play a role in regulating SVZ neurogenesis in the ventral SVZ (27). Consequently, this study sheds light on the role of cholinergic signaling and the specific molecular mechanisms involved in the regulation of ventral LV NSCs activation and proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the recent discovery of a direct neural connection between the ACC and the subventricular zone (SVZ), responsible for olfactory neurogenesis, has sparked interest in the ACC's potential role in this process (Figure 1). [9] Therefore, it is imperative to conduct further research on the ACC's involvement in olfactory neurogenesis, as it holds the promise of providing valuable insights into brain functions and neuronal plasticity.…”
Section: F I G U R Ementioning
confidence: 99%